Role of circRNA circ_0000080 in myocardial hypoxia injury. Issue 4 (1st April 2022) - Wang, Bo; Zhang, Yuyang; Fang, Shunmiao; Wang, Hui
ABSTRACT: This study aimed to investigate the potential role of circRNA circ_0000080 in myocardial hypoxia injury and the underlying mechanisms. Patients with myocardial hypoxia injury who were admitted to Xi'an No. 1 Hospital, China, were included in this study. The expression levels of circ_0000080, miR-367-5p, and COX2 were analyzed by real-time quantitative PCR (RT-qPCR); cell viability was measured by cell counting kit-8 (CCK-8) assay; and apoptosis was detected by flow cytometry. In addition, the release of cytokines was determined by Enzyme-linked immunosorbent assay (ELISA), and the binding sites between miR-367-5p and circ_0000080/ COX2 were predicted by bioinformatics analysis and confirmed by dual-luciferase reporter and RNA pull-down assays. circ_0000080 was upregulated in patients with MI and in H9c2 cells treated with H2 O2 and hypoxia/reoxygenation (H/R). Silencing circ_0000080 reduced the H/R-mediated apoptosis of cardiomyocytes and secretion of pro-inflammatory cytokines. Moreover, circ_0000080 functioned as an miR-367-5p sponge to regulate the expression of COX2 . Downregulated miR-367-5p or overexpressed COX2 degraded cellular functions of cardiomyocytes. circ_0000080 knockdown alleviated myocardial hypoxia injury through the miR-367-5p/ COX2 axis. Graphical abstract: uf0001